Implementation of reliability centred maintenance in maintaining medical equipment in hospital - Siti Hajar Salim,; Saiful Amri Mazlan,; Siti Aisyah Salim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Maintenance services are performed to ensure the equipment is operating according to manufacturer standard and maintained at desired level of quality. The implementation of properly scheduled of maintenance services may prevent unexpected breakdown and disruption of operational in a hospital. However, in some cases, series of breakdown occurred with the maintenance services in-place. This raised the doubts on the reliability and effectiveness of the maintenance services that being exercised. In general, there are many types of maintenance services nonetheless which suit best for medical equipment need to be identified. This paper is to identify the right maintenance services for medical equipment in hospital using Reliability Centred Maintenance (RCM). The equipment was selected based on the criticality and the breakdown history. Failure factors of breakdown were identified and based on this data, a right maintenance services were recommended for the further action.